Shared Mobility and Automated Vehicles : Responding to Socio-Technical Changes and Pandemics. - Khan, Ata M., 1941- (Institution of Engineering & Technology, 2022)
Shared mobility is gaining increasing attention in private and public sectors. Serving as a source of information on how best to shape shared vehicle systems of the future, this book contributes knowledge on key facets of shared mobility. It includes shared vehicle systems as well as shared automated vehicle systems.
Keywords: Automated vehicles.; Transportation -- Social aspects.; Transportation -- Environmental aspects.; elektronické knihy; electronic books